2019
DOI: 10.1021/acs.est.8b04718
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-Based Recycling of Flavins Allows Shewanella oneidensis MR-1 To Yield Energy from Metal Reduction Across Physical Separations

Abstract: We fabricated a microfluidic reactor with a nanoporous barrier to characterize electron transport between Shewanella oneidensis MR-1 and the metal oxide birnessite across a physical separation. Real-time quantification of electron flux across this barrier by strains with different electron transfer capabilities revealed that this bacterium exports flavins to its surroundings when faced with no direct physical access to an electron acceptor, allowing it to reduce metals at distances exceeding 60 μm. An energy b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 43 publications
1
22
0
Order By: Relevance
“…As ATP represents the energy stored from the intracellular redox reactions of bacteria 22 , the metabolic activity of the cells with/without the CDs' addition was further evaluated by an ATP assay ( Fig. 6b).…”
Section: Resultsmentioning
confidence: 99%
“…As ATP represents the energy stored from the intracellular redox reactions of bacteria 22 , the metabolic activity of the cells with/without the CDs' addition was further evaluated by an ATP assay ( Fig. 6b).…”
Section: Resultsmentioning
confidence: 99%
“…The use of iron oxides as terminal electron acceptors in anaerobic microbial respiration is central to biogeochemical element cycling and pollutant transformations in many suboxic and anoxic environments ( 1 6 ). To ensure efficient electron transfer to solid-phase ferric iron, Fe(III), at circumneutral pH, metal-reducing microorganisms from diverse phylae use dissolved extracellular electron shuttle (EES), including quinones ( 7 9 ), flavins ( 10 16 ), and phenazines ( 17 19 ), to transfer two electrons per EES molecule from the respiratory chain proteins in the outer membrane of the microbial cell to the iron oxide ( 17 , 20 , 21 ). The oxidized EES can diffuse back to the cell surface for rereduction, thereby completing the catalytic redox cycle involving the EES.…”
mentioning
confidence: 99%
“…For example, S. oneidensis can facilitate electron transfer directly via outer membrane c-type cytochromes (c-Cyts) in contact with iron (oxyhyr)­oxides, or indirectly via electron shuttles that can diffuse between c-Cyts and ferric (oxyhydr)­oxides to mediate electron transfer . Recent work has shown that naturally occurring electron shuttles can diffuse over micrometer to centimeter distances to transfer electrons, , and for centimeter-scale mass transfer distances the iron (oxyhydr)­oxide reduction rates will likely be diffusion controlled.…”
Section: Discussionmentioning
confidence: 99%